Mathematics Research in Association of Southeast Asian Nations Countries: A Scientometric Analysis of Patterns and Impacts - Ho-Le, Thao P.; Nguyen, Tuan V. (Frontiers in Research Metrics and Analytics, 2018)
In this study, we aimed at mapping the trend and impact of mathematics research originated from Association of Southeast Asian Nations (ASEAN) countries by using a scientometric approach. We extracted the Web of Science’s article-level data of all publications concerning mathematics research during the period of 2006–2015 for ASEAN countries. The impact of research was assessed in terms of citation, and the pattern of international collaboration was mapped by the presence of coauthorship and international affiliations. During the coverage period, ASEAN countries had published 9,890 papers in mathematics, accounting for 3.8% of total ISI-indexed publications from the region. Almost 95% of the mathematics publication was from Singapore (4,107 papers), Vietnam (2,046), Malaysia (1,927), and Thailand (1,317). Approximately 54% of mathematics papers from ASEAN countries had international coauthorship, and these papers had greater yearly citation rate than those without international collaboration. With the exception of Singapore, the citation rate for other ASEAN countries was below the world average by 8–30%. The most important predictor of citations was journal impact factor, which accounted for 5.2% of total variation in citations between papers. These findings suggest that the contribution of ASEAN countries as a group to mathematics research worldwide is modest in terms of research output and impact.